Pengaruh Kepercayaan, Kualitas Produk dan Citra Merek Terhadap Kepuasan Konsumen Pada PT Batam Frozen Food - Eric Eric; Nora Pitri Nainggolan (Komunitas Dosen Indonesia, 2023)
The aims of this studies are determining the effects of trust, product quality, and brand image on consumer satisfaction at PT Batam Frozen Food. The researches samples using 100 consumers at PT Batam Frozen Food used the Cochran formula. Questionnaires are using as data collections techniques. By using SPSS 25 software, data analysis techniques include descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis testing. Based on the results of multiple linear regression, trust (X1) has an effect of 0.340 or 34% on consumer satisfaction at PT Batam Frozen Food, product quality (X2) has an effect of 0.217 or 21.7% on customer satisfaction at PT Batam Frozen Food and brand image ( X3) has an effect of 0.477 or 47.7% on consumer satisfaction at PT Batam Frozen Food. Apart from this, trust, product quality, and brand image affect consumer satisfaction at PT Batam Frozen Food by 62.7% according to the coefficient of determination data (R2). Based on the results of hypothesis testing, it was found that trust, product quality, and brand image had a positive and significant effect partially or simultaneously on customer satisfaction at PT Batam Frozen Food.